Storytelling as an Educational Tool to Improve Language Acquisition: A Review of the Literature - Ghafar, Zanyar (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
Storytelling is a well-established means of social interaction, and a wealth of studies has shown its effectiveness as a teaching technique for improving language skills in first (L1) and second (L2) language development, regardless of the age or background of the learners. Furthermore, it is said that storytelling is a more effective method of teaching languages than traditional teaching materials like textbooks. Research generally suggests that the reason storytelling works so well is because it is entertaining, interesting, and very memorable. This makes students want to hear more stories and gets them talking, writing, and reading about them. However, the research that has already been done and published in the literature sometimes needs more detailed information on the techniques used to measure the effects of storytelling or the exact skills that are developed via its application. Furthermore, the vast majority of studies neglect to investigate any potential negative consequences of storytelling on language acquisition, leaving us with the impression that it is a teaching strategy that solely has beneficial impacts on learning a second language. The goal of this review of the literature is to provide a thorough overview of empirical research on the effects of storytelling on L2 language learning. It also seeks to contrast storytelling's efficacy with that of other instructional strategies. It also seeks to identify gaps in the current literature that need to be filled up by future studies. By looking at these questions, scholars and teachers will have a clearer understanding of the value of storytelling in language learning environments, which will help them improve as teachers.